PENINGKATAN KETERAMPILAN BERHITUNG MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL SISWA KELAS III SDN GONDANGDIA 01 PAGI - Shinta Nurhalimah; Chrisnaji Banindra Yudha; Juhana Sakmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aimed to enhance students’ multiplication numeracy skills through the Implementation of the Problem Based Learning model assisted by Wordwall media among the III B students of SDN Gongdangdia 01 Pagi. The study involved 31 students’ as participants and was conducted from late August during the first semester of 2025/2026. The research employed the Classroom Action Research approach based on the Kemmis and Mc. Taggart model, which consists of four cyclical stages: Planning, Acting, Observing, and Reflecting. Data were collected through observation and testing anf analyzed by calculating the percentage score of teacher and student activities, as well as the students’ multiplication skill tests at the end of each cycle. The findings indicated a significant improvement in students’ multiplication numeracy skills through the use of the Problem Based Learning model assisted by Wordwall media. In cyles I and II, the students’ numeracy skills test results had a completenees percentage of 56.08% and 90,32%. The percentage of teacher percentage activity monitoring results in cycles I and II was 70% and 88%, respectively while the percentage of student activity in cycles I and II wa 62% and 84%.